2020
DOI: 10.1097/nhh.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Therapy on Reduction of Bacterial Colonies and Acceleration of Diabetic Foot Ulcer Healing

Abstract: Diabetic foot ulcers (DFUs) are highly vulnerable to infection and pose risk for limb amputations. Studies have shown that ozone therapy reduces wound size and improves wound healing time better than standard treatments. We examined the effectiveness of combining standard wound care with ozone therapy to reduce bacterial colonization and accelerate healing of DFUs in the home care setting. The control group (n = 12) received standard wound care with antimicrobial dressings every 3 days for 21 days, and the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…In recent years, there has been a growing interest in the scientific literature about the biochemical properties of the O 2 O 3 mixture in order to better understand the basic mechanisms of action underpinning its systemic effects on human blood and tissues [10][11][12][13]. Several papers suggested relevant medical features of O 3 , including bactericidal and virucidal properties, inflammatory modulation and circulatory stimulation, with multiple applications in several medical fields including wound healing, ischemic disorders, infections and chronic inflammatory conditions like musculoskeletal disorders [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the scientific literature about the biochemical properties of the O 2 O 3 mixture in order to better understand the basic mechanisms of action underpinning its systemic effects on human blood and tissues [10][11][12][13]. Several papers suggested relevant medical features of O 3 , including bactericidal and virucidal properties, inflammatory modulation and circulatory stimulation, with multiple applications in several medical fields including wound healing, ischemic disorders, infections and chronic inflammatory conditions like musculoskeletal disorders [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 presents an overview of the included clinical trials and Table 1 summarizes the most relevant data and main results from each study. [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…A general analysis of clinical trials results suggests a positive response to the use of ozone therapy in the investigated dermatological conditions. The patients received ozone therapy by gaseous ozone[ 18 19 20 23 24 25 26 ] or incorporated in different vehicles such as water,[ 22 28 30 ] gel[ 24 ] and oil. [ 21 27 28 29 30 31 33 34 ] Only in three clinical trials ozone was not used topically, but were used through subcutaneous,[ 35 ] intralesional,[ 22 ] intravenous[ 22 32 ] and rectal[ 32 ] routes.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the effect of ozone therapy on reducing bacterial colonization and healing of DFUs in patients with second- and third-degree DFUs. They showed that routine care combined with ozone therapy can have a significant effect on the healing of DFUs in these patients [ 8 ]. Rosul et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown the effectiveness of ozone therapy in treating infections and wounds because of its antimicrobial properties [ 2 , 8 ], the extensive use of this method as a treatment is restricted due to its side effects, including toxic effects on the respiratory tract [ 6 ]. It should be noted that these side effects are dose-dependent, and application requires a closed system ensuring no escape of ozone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%